Human capital utilisation, quiet quitting and employee retention - Giovanni Russo (Publications Office of the European Union, 2024)
When employees leave an organisation, they take their human capital with them. They also take with them any investment that the training organisation may have done to enhance their human capital, both in terms of firm-specific and general skills. Employee turnover is the main cause of the under-provision of training in organisations. However, the returns on organisational investments in human capital are also jeopardised by the under-utilisation of skills. This happens when employees withhold work effort and display forms of organisational withdrawal (quiet quitting). Turnover can be regarded as an extreme manifestation of quiet quitting. Organisations vary in their reliance on human capital for their success; this heterogeneity affects turnover, too, while those relying on human capital for their success encourage workers to draw on their skills (and discourage quiet quitting). The encouragement to perform serves to turn the human capital of individual workers into an organisational resource. The inducements offered to support performance decrease the likelihood of quiet quitting, and turnover. Turnover is a threat to the returns on organisational investments in human capital. However, the threat is less acute in organisations relying on human capital for their success.
Keywords: 370; employee turnover; motivation; quiet quitting; human capital; skills utilisation; skills development; wage earner; job satisfaction; vocational training; business policy; updating of skills